Medical Respite and Linkages to Outpatient Health Care Providers among Individuals Experiencing Homelessness. Issue 2 (2nd April 2016) - Zur, Julia; Linton, Sabriya; Mead, Holly
ABSTRACT: Medical respite programs provide nursing care and case management to individuals experiencing homelessness following hospitalization for an acute medical problem. One goal of these programs is to link clients to outpatient providers to decrease their reliance on hospital services. Through qualitative interviews with staff members ( n = 8) and clients ( n = 14) at a medical respite program, we explored processes of, and challenges associated with, linking clients to outpatient care. Six themes were identified, which offer insight about important considerations when linking clients to outpatient providers and highlight the value of medical respite programs for this population.